Ethical surgical placebo-controlled trials of deep brain stimulation for treatment-resistant anorexia nervosa. - Pugh, J; Maslen, H; Savulescu, J (Elsevier, 2017)
Lipsman et al. present promising data concerning Deep Brain Stimulation (DBS) in the management of chronic, treatment-resistant anorexia nervosa (AN).(1) They conclude with a call for a placebo-controlled, randomised trial in this context.